Quality Analysis Of Cow Milk Kefir With Addition Of Purple Sweet Potato Puree - Miftah Al Fattaah; Anni Faridah; Yuliana Yuliana; Sari Mustika (Universitas Negeri Padang, 2025)
Kefir is a fermented milk product characterized by a tangy, slightly alcoholic, and carbonated profile, produced through the symbiotic activity of lactic acid bacteria and yeasts. It naturally contains probiotics that exert beneficial effects on health. The anthocyanins present in purple sweet potato (Ipomoea batatas L.) exhibit prebiotic potential. This study aimed to evaluate the organoleptic quality of kefir supplemented with purple sweet-potato purée. A single-factor completely randomized design was employed, comprising four treatments (0 %, 15 %, 20 %, and 25 %) with three replications. Thirty trained panelists from the Family Welfare Education Study Program, Universitas Negeri Padang, assessed color, aroma, texture, flavor, and overall acceptance. Data were analyzed by one-way ANOVA followed by Duncan’s multiple-range test (α = 0.05). Results revealed that purée concentration significantly (p < 0.05) influenced purple color intensity, whereas aroma, texture, and flavor remained unaffected. The 25 % (X3) treatment yielded the best overall sensory profile. Consequently, supplementation of cow’s-milk kefir with 25 % purple sweet-potato purée can be recommended to produce an attractively colored, probiotic beverage with high consumer acceptability.